Performance evaluation of hydrophilic organic polymer sorbents for desiccant air-conditioning applications - Muhammad Sultan; Takahiko Miyazaki; Shigeru Koyama; Zahid M Khan (Adsorption Science & Technology)
The present study provides performance evaluation of two kinds of crosslinked hydrophilic organic polymer sorbents (PS-I and PS-II) for desiccant air-conditioning applications. In this regard, optimum temperature and humidity zones are established for various air-conditioning applications which include (i) humans’ thermal comfort, (ii) animals’ thermal comfort, and (iii) postharvest storage of fruits/vegetables. Honeycomb-like desiccant blocks composed of PS-I/PS-II are assumed for numerical simulation analysis. The numerical simulation model is programmed into MATLAB which utilizes the scientific relationships of adsorption isotherms, adsorption kinetics, isosteric heat of adsorption, and thermophysical properties for each sorbent. A particular desiccant air-conditioning system design is proposed, and numerical simulation has been conducted for the performance evaluation of PS-I and PS-II. According to the results, PS-I enables higher dehumidification than PS-II at low regeneration temperature (50℃) and cycle time of 60:90 min. It is because the PS-I possesses better water vapor sorption kinetics as compared to PS-II. Although the PS-II enabled higher steady-state adsorption amount but it could not influence the overall system performance. On the other hand, the optimum performance by the PS-II is limited to relatively long cycle time and higher regeneration temperature (≥80℃). It has been concluded that the PS-I is relatively better choice for desiccant air-conditioning, and consequently can be considered for various air-conditioning applications. Furthermore, effects of mass flow rate, isosteric heat of adsorption, regeneration temperature, and cycle time on air humidity ratio and air temperature profiles have been discussed in order to highlight the performance variability of desiccant air-conditioning system.